Family business models : practical solutions for the family business - Gimeno, Alberto; Baulenas, Gemma; Coma-Cros, Joan. (New York : Palgrave MacMillan, 2010)
This text contains a unique new model for understanding family businesses, giving readers the potential to build better managed and more stable family firms and to plan for a successful future.
Includes bibliographical references and index.
Keywords: Family-owned business enterprises -- Management